Case Report: Osteomyelitis in a giant panda (Ailuropoda melanoleuca) - Wang, Chengdong; Yang, Haidi; Wu, Kai; Deng, Linhua; Li, Chengyao; Wei, Rongping; Li, Caiwu; Zhu, Yan; Wei, Ming; Huang, Zhi; Cheng, Yanxi; Chen, Xuemei; et al. (Frontiers in Veterinary Science, 2025)
Osteomyelitis is an inflammatory disease of bone tissue induced by microbial infection, and poses a significant health burden in humans and animals. The global annual incidence in humans is estimated ~1–10 cases per 100,000 individuals, with notably higher rates observed in high-risk populations. In domestic cubs and companion animals, trauma-related osteomyelitis can occur at an incidence rate ranging from 0.1 to 5%. Although osteomyelitis is well-documented in both human and veterinary medicine, with diverse and complex diagnostic and therapeutic approaches available for human cases, it has not been previously reported in the giant panda (Ailuropoda melanoleuca). This report presents a case of osteomyelitis in an elderly giant panda exhibiting lameness in the left hind limb. Diagnosis was confirmed trough laboratory testing, computed tomography (CT), and magnetic resonance imaging (MRI). The animal underwent a 2-month course of treatment with rifampicin (Guangzhou Baiyunshan Pharmaceutical Group Co., LTD) and medical-grade chitosan (Qingdao Jintieshan Biotechnology Co., LTD), which resulted in significant clinical improvement. This retrospective case analysis provides valuable insights into the clinical diagnosis and management of osteomyelitis in giant pandas and contributes to the foundational knowledge necessary for the prevention and treatment of this condition in captive populations.